Self and Social Alienation in Murakami’s Colorless Tsukuru Tazaki and His Years Of Pilgrimage - Muhamad Rafy Adityana (Passage, 2018)
Isolation and estrangement is probably still one of the most recurring themes in today’s literature. Haruki Murakami, a renowned contemporary novelist, often adapted the theme of alienation and the endless search for true freedom in his works. Written as a a bildungsroman novel by depicting the life of a troubled young adult protagonist, Colorless Tsukuru Tazaki and His Years of Pilgrimage is Murakami’s recent work which also highlights the alienation issue. Abandoned by his group of close friends without any apparent reason, Tsukuru is haunted by the feeling of loneliness and unreasonable guilt which drives him to yearn for death. Employing Irene Taviss’ (1969) theory as a framework, this study aims to discuss the representation of social and self-alienation of the main characters in the latest Haruki Murakami’s novel. It is shown that Tsukuru experiences both social and self-alienation that estranges and also torments him mentally. Moreover, the findings also discover that Tsukuru’s self-alienation is mostly triggered by the social alienation event that he experienced in the past, representing that self and social alienation is interlinked to each other. Keywords: Social and self-alienation, escapist resolutions